Comprehensive evaluation of microneedle‐based intradermal adalimumab delivery vs. subcutaneous administration: results of a randomized controlled clinical trial. Issue 8 (2nd February 2021) - Jacobse, Justin; ten Voorde, Wouter; Tandon, Anushka; Romeijn, Stefan G.; Grievink, Hendrika W.; van der Maaden, Koen; van Esdonk, Michiel J.; Moes, Dirk Jan A.R.; Loeff, Floris; Bloem, Karien; de Vries, Annick; Rispens, Theo; et al.
Abstract : Aims: To evaluate feasibility of intradermal (i.d.) adalimumab administration using hollow microneedles, and to compare a single i.d. dose of adalimumab using a hollow microneedle with a single subcutaneous (s.c.) dose using a conventional needle. Methods: In this single‐centre double‐blind, placebo‐controlled, double‐dummy clinical trial in 24 healthy adults we compared 40 mg adalimumab (0.4 mL) administered i.d. using a hollow microneedle with a s.c. dose using a conventional needle. Primary parameters were pain, acceptability and local tolerability; secondary parameters safety, pharmacokinetics and immunogenicity. We explored usability of optical coherence tomography, clinical photography, thermal imaging, and laser speckle contrast imaging to evaluate skin reaction after i.d. injections. In vitro protein analysis was performed to assess compatibility of adalimumab with the hollow microneedle device. Results: While feasible and safe, injection pain of i.d. adalimumab was higher compared to s.c. adalimumab (35.4 vs . 7.9 on a 100‐point visual analogue scale). Initial absorption rate and relative bioavailability were higher after i.d. adalimumab (time to maximum plasma concentration = 95 h [47–120]; Frel = 129% [6.46%]) compared to s.c. adalimumab (time to maximum plasma concentration = 120 h [96–221]). Anti‐adalimumab antibodies were detected in 50% and 83% of the subjects after i.d. and s.c. adalimumab, respectively. We observed statistically significantly more erythema and skin perfusion after i.d. adalimumab, compared to s.c. adalimumab and placebo injections ( P < .0001). Cytokine secretion after whole blood lipopolysaccharide challenge was comparable between administration routes. Conclusions: Intradermal injection of adalimumab using hollowing microneedles was perceived as more painful and less accepted than s.c. administration, but yields a higher relative bioavailability with similar safety and pharmacodynamic effects.